DESIGN AND MANUFACTURE CHASSIS AND BODY OF SIMPLE GOKART USING AUTOMATIC CLUTCH AND 7.5 HP ENGINE POWER - N. Nazaruddin; Dedy Masnur; Erwin Ardiansyah (Sekolah Tinggi Teknologi Wastukancana, 2020)
Go-kart is a variant of a simple and small open-roof four-wheeled vehicle for motor sports. Go-kart usually races on small scale circuits. Go-kart racing is usually considered a stepping stone for motor sports that are higher and more expensive. The design of the karts is carried out by mechanical engineering students of the University of Riau based on the size of karts in general. The chassis is made of pipe with ASTM A53 pipe specifications with a tensile strength of 240 MPa with a dimension of length of 6.22 meters, an outer diameter of 33.40 mm and an inner diameter of 30.02 mm. Body building is done with fiber with a catalyst mixture ratio of 1:45. The process of painting with a ratio of primers and hardeners is 1: 4, and clear and hardener 4: 1. A kart with a chassis mass of 7.09 kg and a passenger of 70 kg has been produced, with dimensions of length 1100 mm, width of 610 mm, and distance between axes of 1050 mm. This karting uses the 1994 Astra grand engine with 7.5 HP of power, 6000 rpm rotation and 20 kg mass. The transmission system used is a double automatic type.